Earnings quality and the cost of debt: A case study of Vietnam - Van Vu Thi Thuy; Hung Dang Ngoc; Tram Nguyen Ngoc; Hoang Anh Le (Cogent Business & Management, 2022)
This paper examines the impact of earnings quality (EQ) on the Vietnam companies' cost of debt (COD). We use data from companies listed on the Vietnam stock market from 2010 to 2019. In this paper, we develop a model to investigate the influence of audit quality and foreign ownership on COD. We find that EQ had a negative relationship with COD. However, when firm is in financial distressed, EQ has a positive relationship with COD. As an intermediate variable, EQ also has a negative relationship with COD.
Keywords: 650; financial constraints; Audit quality; foreign ownership; cost of debt; earnings quality